Coal gangue-based composite material as well as preparation method and application thereof

By using coal gangue-based composite materials, combined with thermal alkali activation and porous material loading technology, the problem of poor nitrogen removal effect in sewage treatment is solved, and efficient and economical sewage treatment effect is achieved.

CN119551810AActive Publication Date: 2025-03-04JIANGSU GUOFENG ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411930963.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-04
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

It is difficult for existing sewage treatment technologies to effectively improve the sewage nitrogen removal effect without changing the original operating process, and traditional methods have problems such as high operating costs and poor effluent water quality.

Method used

Coal gangue-based composite materials are used to activate coal gangue by cetyl trimethylammonium bromide to enhance its hydrophobicity and adsorption. Combined with kaolin, carboxymethylcellulose and activated carbon, a composite structure with porous materials is formed to improve microbial activity and pollutant degradation ability.

Benefits of technology

It significantly improves the denitrification efficiency in sewage, reduces operating costs, avoids secondary pollution of effluent, and enhances the sewage treatment effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551810A_ABST
    Figure CN119551810A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sewage treatment, and particularly relates to a coal gangue-based composite material as well as a preparation method and application thereof. According to the preparation method, positive charge groups on the surface of hexadecyl trimethyl ammonium bromide are adsorbed on negative charge points on the surface of the coal gangue, and hydrophobic long carbon chains form an organic phase in a hydrophobic bond form, so that the hydrophobicity of the coal gangue activated by the hot alkali is enhanced, and the adsorbability on organic pollutants is remarkably enhanced. Carboxymethyl cellulose has excellent biocompatibility and environmental friendliness, has a large number of active groups on the surface, and can provide donors for coordination reaction of metal cations. The coal gangue contains various metal elements (Fe, Ca, Mg and the like) and can form a metallic bond with a negative active group on carboxymethyl cellulose, and the coal gangue and the negative active group are matched with each other, so that the loading capacity of microorganisms on the composite material can be increased, the utilization rate of an organic carbon source in sewage can be increased, and the sewage treatment efficiency of the composite material can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sewage treatment, and specifically relates to a gangue-based composite material and a preparation method and application thereof. Background Art

[0002] In recent years, with the promulgation of the Ten Water Regulations and the continuous advancement of ecological civilization construction, the sewage treatment effluent indicators have become higher and higher, and the local standards have become more and more stringent. The national Class A standard (COD: 50mg / L, TN: 15mg / L) is increasingly difficult to meet the increasingly stringent effluent indicators. The Class A sewage discharge standard in Zhejiang, Jiangsu and other places has a TN discharge limit of 10mg / L and a COD discharge limit of 30mg / L. However, some sewage plants are still using some old treatment methods and operating processes, so it is urgent to improve the sewage treatment effect.

[0003] The general methods for treating wastewater include physical and chemical methods, chemical methods and biological methods. Biological methods are widely used due to their good treatment effects, low energy consumption and strong economic applicability. Biological methods are divided into activated sludge methods and biofilm methods. Among them, the activated sludge method has become the mainstream method for treating wastewater in sewage treatment plants due to its good treatment effects, low treatment costs and strong applicability. The traditional activated sludge method is based on activated sludge. The most common AAO method uses aerobic tanks to degrade COD, anoxic tanks to denitrify, and anaerobic tanks to release phosphorus. If the carbon source in the anoxic tank is insufficient, it will be difficult to maintain high efficiency in the anoxic denitrification process. The additional addition of carbon sources will increase operating costs and deteriorate the effluent quality. In addition, the cost of infrastructure construction for upgrading and rebuilding traditional sewage treatment plants is high. Therefore, seeking a method to enhance the denitrification effect of sewage without changing the original operating process has become a hot topic in recent years.

[0004] The preparation of efficient biological fillers is a simple, economical and convenient method to enhance the denitrification of sewage. It can meet the discharge requirements without changing the basic facilities of the sewage treatment plant. The prior art discloses a preparation method and application of immobilized bacteria and algae biological fillers. Iron-carbon materials are added to the immobilized bacteria and algae biological fillers. Due to the micro-electrolysis of the iron-carbon materials, the iron ions produced can participate in the electron transfer between microbial cells, enhance the respiration of microorganisms, and help increase biomass and improve the degradation capacity of the bacteria and algae symbiotic system for pollutants. Although nitrogen and phosphorus can be removed simultaneously, the reproduction of algae is limited, and only nitrogen and phosphorus pollutants with a lower load can be processed. At the same time, carbon sources need to be supplemented, and there is a possibility of secondary pollution. Without fundamentally strengthening the activity of microorganisms and increasing the abundance of populations, it is difficult to further improve the denitrification effect. The prior art also discloses a sulfur / pyrrhotite composite biological filler for denitrification and phosphorus removal, and its preparation method and application. The biological filler is obtained by granulating sulfur, pyrrhotite and shells by physical methods. The sulfur in the composite biological filler can be used as an electron donor for autotrophic denitrification. The pyrrhotite, whose main component is FeS, can not only be used as an electron donor for microbial denitrification, but also the released iron ions can form iron phosphate precipitation with phosphate to achieve the purpose of simultaneous denitrification and phosphorus removal. At the same time, the shell has the function of adaptively adjusting pH. However, the sulfur / pyrrhotite itself has a complex composition and contains a variety of heavy metal substances, and the effluent is prone to excessive heavy metals.

[0005] Therefore, how to produce clean, green and efficient microbial fillers that can not only supplement carbon sources to a certain extent without causing secondary pollution to the effluent, but also enhance the activity of denitrification microorganisms, provide necessary nutrients for the denitrification process, improve the ability to degrade pollutants, and increase the efficiency of microbial denitrification is a problem to be solved. Summary of the invention

[0006] The purpose of the present invention is to provide a gangue-based composite material and a preparation method and application thereof.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a gangue-based composite material, comprising a gangue matrix material and a porous material loaded on the surface and in the pores of the gangue matrix material;

[0009] The raw materials for preparing the coal gangue matrix material include coal gangue, kaolin, carboxymethyl cellulose, hexadecyltrimethylammonium bromide, a binder, a surfactant and polydiallyl phthalate.

[0010] Preferably, the raw materials for preparing the coal gangue matrix material include, by weight, 40 to 50 parts of coal gangue, 2 to 6 parts of kaolin, 10 to 20 parts of carboxymethyl cellulose, 10 to 20 parts of cetyltrimethylammonium bromide, 5 to 10 parts of adhesive, 7 to 12 parts of surfactant and 4 to 8 parts of polydiallyl phthalate.

[0011] Preferably, the adhesive comprises one or more of unsaturated polyester resin, phenolic resin, polyvinyl alcohol, α-cyanoacrylate, acrylate and epoxy resin.

[0012] Preferably, the surfactant includes one or more of sodium dodecyl sulfate and sodium dodecyl silicate.

[0013] Preferably, the particle size of the coal gangue is 100-200 mesh;

[0014] The porous material includes activated carbon;

[0015] The particle size of the porous material is 100-200 meshes; the mass ratio of the coal gangue to the porous material is 40-50:20-35.

[0016] Preferably, the gangue-based composite material is a porous material, and the porosity of the gangue-based composite material is 50-60%.

[0017] The present invention also provides a method for preparing the gangue-based composite material described in the above technical solution, comprising the following steps:

[0018] Using cetyltrimethylammonium bromide to perform hot alkali activation on coal gangue to obtain activated coal gangue;

[0019] The activated coal gangue, kaolin, carboxymethyl cellulose, a binder and a porous material are mixed to obtain a mixture;

[0020] The mixed material, surfactant and polydiallyl phthalate are mixed and then melt-granulated to obtain the gangue-based composite material.

[0021] Preferably, the temperature of the hot alkali activation is 100-200° C. and the time is 40-60 min.

[0022] Preferably, the temperature of the melt granulation is 800-1000° C., and the insulation time is 1-2 hours.

[0023] The present invention also provides the use of the gangue-based composite material described in the above technical solution or the gangue-based composite material prepared by the preparation method described in the above technical solution in sewage treatment.

[0024] The invention provides a gangue-based composite material, comprising a gangue matrix material and a porous material loaded on the surface and in the pores of the gangue matrix material; the raw materials for preparing the gangue matrix material include gangue, kaolin, carboxymethyl cellulose, hexadecyltrimethylammonium bromide, an adhesive, a surfactant and polydiallyl phthalate.

[0025] In the present invention, the positively charged groups on the surface of hexadecyl trimethyl ammonium bromide are adsorbed on the negatively charged sites on the surface of coal gangue, and the hydrophobic long carbon chains form an organic phase in the form of hydrophobic bonds with each other, so that the hydrophobicity of the coal gangue after hot alkali activation is enhanced, and the adsorption capacity of organic pollutants is significantly enhanced. Carboxymethyl cellulose has excellent biocompatibility and environmental friendliness, and has a large number of active groups on the surface, which can provide donors for the coordination reaction of metal cations. Coal gangue contains a variety of metal elements (Fe, Ca and Mg, etc.), which can form metal bonds with the negative active groups on carboxymethyl cellulose, and the two cooperate with each other, which can increase the loading of microorganisms on the composite material, improve the utilization rate of organic carbon sources in sewage, and then improve the treatment efficiency of the composite material to sewage. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a diagram showing the effect of the gangue-based composite material obtained in Example 1 on pollutant removal;

[0027] Figure 2 This is a diagram showing the effect of the gangue-based composite material obtained in Example 2 on pollutant removal;

[0028] Figure 3 This is a diagram showing the removal effect of pollutants by the gangue-based composite material obtained in Example 3. DETAILED DESCRIPTION

[0029] The present invention provides a gangue-based composite material, comprising a gangue matrix material and a porous material loaded on the surface and in the pores of the gangue matrix material;

[0030] The raw materials for preparing the coal gangue matrix material include coal gangue, kaolin, carboxymethyl cellulose, hexadecyltrimethylammonium bromide, a binder, a surfactant and polydiallyl phthalate.

[0031] In the present invention, the raw materials for preparing the coal gangue matrix material preferably include 40-50 parts of coal gangue, 2-6 parts of kaolin, 10-20 parts of carboxymethyl cellulose, 10-20 parts of cetyltrimethylammonium bromide, 5-10 parts of adhesive, 7-12 parts of surfactant and 4-8 parts of polydiallyl phthalate, calculated by weight.

[0032] In terms of mass fractions, the raw material provided by the present invention preferably includes 40 to 50 parts of coal gangue, specifically 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts, and 50 parts. Based on the mass fractions of the coal gangue, the raw material provided by the present invention preferably includes 2 to 6 parts of kaolin, specifically 2 parts, 3 parts, 4 parts, 5 parts, and 6 parts. Based on the mass fractions of the coal gangue, the raw material provided by the present invention preferably includes 10 to 20 parts of carboxymethyl cellulose, specifically 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, and 20 parts. Based on the mass fraction of the coal gangue, the raw material provided by the present invention preferably includes 10 to 20 parts of hexadecyl trimethyl ammonium bromide, specifically 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, and 20 parts. Based on the mass fraction of the coal gangue, the raw material provided by the present invention preferably includes 5 to 10 parts of adhesive, specifically 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, and 10 parts. Based on the mass fraction of the coal gangue, the raw material provided by the present invention preferably includes 7 to 12 parts of surfactant, specifically 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, and 12 parts. Based on the mass fraction of the coal gangue, the raw material provided by the present invention preferably includes 4 to 8 parts of polydiallyl phthalate, specifically 4 parts, 5 parts, 6 parts, 7 parts, and 8 parts.

[0033] In the present invention, the adhesive preferably includes one or more of unsaturated polyester resin, phenolic resin, polyvinyl alcohol, α-cyanoacrylate, acrylate and epoxy resin.

[0034] In the present invention, the surfactant preferably includes one or more of sodium dodecyl sulfate and sodium dodecyl silicate. In the present invention, the stability of the composite material structure can be further improved by adding surfactant and polydiallyl phthalate.

[0035] In the present invention, the kaolin preferably includes titanium minerals and organic matter, and the organic matter preferably includes plant fiber. The present invention has no special limitation on the content of the titanium minerals and organic matter, and those known to those skilled in the art can be used.

[0036] In the present invention, the particle size of the coal gangue is preferably 100-200 meshes, and more preferably 120-140 meshes.

[0037] In the present invention, the porous material preferably includes activated carbon; the particle size of the porous material is preferably 100-200 mesh, and more preferably 120-140 mesh; the mass ratio of the coal gangue to the porous material is preferably 40-50:20-35.

[0038] In the present invention, the gangue-based composite material is preferably a porous material, and the porosity of the gangue-based composite material is preferably 50-60%.

[0039] The present invention also provides a method for preparing the gangue-based composite material described in the above technical solution, comprising the following steps:

[0040] Using cetyltrimethylammonium bromide to perform hot alkali activation on coal gangue to obtain activated coal gangue;

[0041] The activated coal gangue, kaolin, carboxymethyl cellulose, a binder and a porous material are mixed to obtain a mixture;

[0042] The mixed material, surfactant and fixative are mixed and then melt-granulated to obtain the gangue-based composite material.

[0043] The present invention uses hexadecyltrimethylammonium bromide to perform hot alkali activation on coal gangue to obtain activated coal gangue. In the present invention, the temperature of the hot alkali activation is preferably 100-200° C., and the time is preferably 40-60 minutes. The present invention has no special limitation on the process of the hot alkali activation, and the process well known to those skilled in the art can be adopted.

[0044] After obtaining the activated coal gangue, the present invention mixes the activated coal gangue, kaolin, carboxymethyl cellulose, a binder and a porous material to obtain a mixture.

[0045] In the present invention, the mixing is preferably performed under stirring conditions, and the stirring speed is preferably 200 rpm.

[0046] After obtaining the mixed material, the present invention mixes the mixed material, a surfactant and polydiallyl phthalate, and then performs melt granulation to obtain the gangue-based composite material.

[0047] In the present invention, the temperature of the melt granulation is preferably 800-1000° C., and the holding time is preferably 1-2 hours. The present invention has no special limitation on the melt granulation process, and the process known to those skilled in the art can be adopted.

[0048] The present invention also provides the use of the gangue-based composite material described in the above technical solution or the gangue-based composite material prepared by the preparation method described in the above technical solution in sewage treatment.

[0049] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0050] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] Example 1

[0052] Preparation:

[0053] The binder is polyvinyl alcohol, the surfactant is sodium dodecyl sulfate, the particle size of the coal gangue is 120-140 meshes, the porous material is activated carbon, and the particle size of the activated carbon is 120-140 meshes; the kaolin includes titanium minerals and plant fibers;

[0054] The raw materials for preparing the coal gangue matrix include 40 parts of coal gangue, 2 parts of kaolin, 20 parts of cetyltrimethylammonium bromide, 20 parts of carboxymethyl cellulose, 5 parts of polyvinyl alcohol, 10 parts of sodium lauryl sulfate, and 5 parts of polydiallyl phthalate, in parts by mass.

[0055] The mass ratio of coal gangue to activated carbon is 40:20;

[0056] The coal gangue is activated by hot alkali at 200°C using hexadecyltrimethylammonium bromide (CTAB) and kept warm for 40 minutes to obtain activated coal gangue; the activated coal gangue, kaolin, activated carbon, hydroxymethyl cellulose and polyvinyl alcohol are stirred and mixed at 200 rpm to obtain a mixture; the mixture is mixed with sodium dodecyl sulfate and polydiallyl phthalate, and then hot-melt granulated at 1000°C for 1 hour to obtain the coal gangue-based composite material with a porosity of 55%.

[0057] Example 2

[0058] Preparation:

[0059] The binder is polyvinyl alcohol, the surfactant is sodium dodecyl sulfate, the particle size of the coal gangue is 120-140 meshes, the porous material is activated carbon, and the particle size of the activated carbon is 120-140 meshes; the kaolin includes titanium minerals and plant fibers;

[0060] In terms of mass, the raw materials for preparing the coal gangue matrix include 45 parts of coal gangue, 3 parts of kaolin, 15 parts of cetyltrimethylammonium bromide, 15 parts of carboxymethyl cellulose, 8 parts of polyvinyl alcohol, 12 parts of sodium lauryl sulfate, and 6 parts of polydiallyl phthalate;

[0061] The mass ratio of coal gangue to activated carbon is 45:25;

[0062] The coal gangue is activated by hot alkali at 200°C using hexadecyltrimethylammonium bromide (CTAB) and kept warm for 40 minutes to obtain activated coal gangue; the activated coal gangue, kaolin, activated carbon, hydroxymethyl cellulose and polyvinyl alcohol are stirred and mixed at 200 rpm to obtain a mixture; the mixture is mixed with sodium dodecyl sulfate and polydiallyl phthalate, and then hot-melt granulated at 1000°C for 2 hours to obtain the coal gangue-based composite material with a porosity of 57%.

[0063] Example 3

[0064] Preparation:

[0065] The binder is polyvinyl alcohol, the surfactant is sodium dodecyl sulfate, the particle size of the coal gangue is 120-140 meshes, the porous material is activated carbon, and the particle size of the activated carbon is 120-140 meshes; the kaolin includes titanium minerals and plant fibers;

[0066] The raw materials for preparing the coal gangue matrix include 50 parts of coal gangue, 5 parts of kaolin, 20 parts of cetyltrimethylammonium bromide, 20 parts of carboxymethyl cellulose, 10 parts of polyvinyl alcohol, 12 parts of sodium lauryl sulfate, and 8 parts of polydiallyl phthalate, in parts by mass.

[0067] The mass ratio of coal gangue to activated carbon is 50:30;

[0068] The coal gangue is activated by hot alkali at 200°C using hexadecyltrimethylammonium bromide (CTAB) and kept warm for 60 minutes to obtain activated coal gangue; the activated coal gangue, kaolin, activated carbon, hydroxymethyl cellulose and polyvinyl alcohol are stirred and mixed at 200 rpm to obtain a mixture; the mixture is mixed with sodium dodecyl sulfate and polydiallyl phthalate, and then hot-melt granulated at 800°C for 1 hour to obtain the coal gangue-based composite material with a porosity of 55%.

[0069] Application Examples

[0070] The enriched anaerobic sludge was placed in three upflow anaerobic sludge blanket reactors (UASB) and the gangue-based composite materials prepared in Examples 1 to 3 were added respectively. After biofilm formation, simulated wastewater containing 50 mg / L nitrate was used as influent and passed into the reactor. The hydraulic retention time was set to 3 h. The UASB reactor used was made of plexiglass, with an inner diameter of 6 cm, a height of 18 cm, and an effective volume of about 0.5 L. The upper three-phase separator was embedded in the reactor at an angle of 45°, and the outer layer was wrapped by a water bath layer, and the water bath water entered from the bottom and exited from the top. The reactor was insulated by the outer water bath layer, and the temperature was controlled at 35 ± 0.2 ° C.

[0071] Figure 1This is a graph showing the effect of the gangue-based composite material obtained in Example 1 on pollutant removal. Figure 2 This is a graph showing the effect of the gangue-based composite material obtained in Example 2 on pollutant removal. Figure 3 This is a diagram showing the effect of the gangue-based composite material obtained in Example 3 on pollutant removal;

[0072] The specific test results are shown in Table 1;

[0073] Table 1 Effect of coal gangue-based composite materials obtained in Examples 1 to 3 on pollutant removal

[0074]

[0075] from Figures 1 to 3 As can be seen from Table 1, the gangue-based composite material provided by the present invention has an excellent denitrification effect.

[0076] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A coal gangue-based composite material, characterized in that: It comprises a coal gangue matrix material and a porous material loaded on the surface and pores of the coal gangue matrix material; The raw materials for preparing the coal gangue matrix material include coal gangue, kaolin, carboxymethyl cellulose, hexadecyltrimethylammonium bromide, a binder, a surfactant and polydiallyl phthalate.

2. The gangue-based composite material according to claim 1, characterized in that: Calculated by weight, the raw materials for preparing the coal gangue matrix material include 40-50 parts of coal gangue, 2-6 parts of kaolin, 10-20 parts of carboxymethyl cellulose, 10-20 parts of hexadecyltrimethylammonium bromide, 5-10 parts of adhesive, 7-12 parts of surfactant and 4-8 parts of polydiallyl phthalate.

3. The gangue-based composite material according to claim 1 or 2, characterized in that: The adhesive comprises one or more of unsaturated polyester resin, phenolic resin, polyvinyl alcohol, α-cyanoacrylate, acrylate and epoxy resin.

4. The gangue-based composite material according to claim 1 or 2, characterized in that: The surfactant includes one or more of sodium dodecyl sulfate and sodium dodecyl silicate.

5. The gangue-based composite material according to claim 1 or 2, characterized in that: The particle size of the coal gangue is 100 to 200 meshes; The porous material includes activated carbon; The particle size of the porous material is 100-200 meshes; the mass ratio of the coal gangue to the porous material is 40-50:20-35.

6. The gangue-based composite material according to claim 1 or 2, characterized in that: The gangue-based composite material is a porous material, and the porosity of the gangue-based composite material is 50-60%.

7. The method for preparing the gangue-based composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Using cetyltrimethylammonium bromide to perform hot alkali activation on coal gangue to obtain activated coal gangue; The activated coal gangue, kaolin, carboxymethyl cellulose, a binder and a porous material are mixed to obtain a mixture; The mixed material, surfactant and polydiallyl phthalate are mixed and then melt-granulated to obtain the gangue-based composite material.

8. The preparation method according to claim 7, characterized in that: The temperature of the hot alkali activation is 100-200° C. and the time is 40-60 minutes.

9. The preparation method according to claim 7, characterized in that: The temperature of the melt granulation is 800-1000° C., and the heat preservation time is 1-2 hours.

10. Use of the gangue-based composite material according to any one of claims 1 to 6 or the gangue-based composite material prepared by the preparation method according to any one of claims 7 to 9 in sewage treatment.